(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The paper presents the key sociodemographic characteristics of youth (gender, age, marital status and number of children) in Bosnia and Herzegovina in the age group of 15-30 years. The paper indicates the importance of this age group for the economic and population development of a society with a case study of Bosnia and Herzegovina. The main goal of this paper is to link quantitative and qualitative indicators and to point out the ungrateful position of youth in modern Bosnian society, which results in a strong desire to emigrate. The paper thematizes the trends of population growth in Bosnia and Herzegovina It also analyzes and provides a picture of the average youth based on data obtained from the 2013 Census and representative surveys with the target population conducted in the previous five years.